Hubungan Peran Perawat sebagai Edukator sengan Kepatuhan Minum Obat pada Pasien Diabetes Melitus Tipe 2 di RSUD Kota Sabang - Jerniwati Ndururu; Karmila Br Kaban; Deka Novia; Siska Agustina; Tio Yohana Renatalis Dakhi; Winarti Winarti (Malahayati Nursing Journal, 2025)
ABSTRACT Diabetes mellitus (DM) is a complex chronic disease caused by continuously elevated blood sugar levels due to insulin deficiency involving carbohydrate, protein and lipid metabolism and the development of microvascular and neurological complications. The purpose of this study was to determine the relationship between the role of nurses as educators with medication compliance in patients with type 2 diabetes mellitus. The type of research used is an analytic descriptive survey with a Cross Sectional design. The population in this study were all patients with type 2 diabetes mellitus at Sabang City Hospital, totaling 168 people. The technique of taking subjects using simple random sampling as many as 63 people. The instrument used in this study was a questionnaire to measure the role of nurses as educators and compliance with taking medication in patients with type 2 DM. The research data analysis was univariate and bivariate analysis with chi square test. The results showed that the majority of nurses' roles were sufficient as many as 33 people (52.4%) and the minority of nurses' roles were good as many as 12 people (19%). The majority of respondents were not compliant with taking medication as many as 34 people (54%) and the minority were compliant with medication as many as 19 people (45.2%). Based on the chi-square test, it was found that there was a relationship between the role of nurses as educators with adherence to taking medication in patients with diabetes mellitus (p = 0.001). The conclusion of this study is that there is a relationship between the role of nurses as educators with adherence to taking medication in patients with diabetes mellitus type 2. Keywords: Nurse's Role, Educator, Medication Adherence, Diabetes Mellitus  ABSTRAK Tingginya angka kejadian Diabetes Mellitus (DM) tidak terlepas dari banyaknya faktor yang memengaruhinya. Dalam menangani faktor risiko dibutuhkan pengetahuan yang memiliki peran yang sangat penting dalam menentukan sikap dan perilaku seseorang.  Selain itu, dukungan keluarga dan spritual juga tidak kalah penting dalam meningkatkan kualitas hidup penderita DM. Tujuan penelitian ini adalah untuk mengetahui hubungan dukungan keluarga dan dukungan spiritual dengan kualitas hidup penderita diabetes mellitus. Jenis penelitian yang digunakan adalah survei bersifat deskriptif analitik dengan rancangan Cross Sectional. Populasi dalam penelitian ini adalah seluruh pasien dengan penyakit DM di RSUD Kota Sabang sebanyak 168 orang. Teknik pengambilan subjek menggunakan simple random sampling sebanyak 63 orang. Instrumen yang digunakan dalam penelitian ini adalah kuesioner untuk mengukur dukungan keluarga, dukungan spiritual dan kualitas hidup pasien DM. Analisa data penelitian adalah analisis univariat dan bivariat dengan uji chi square. Hasil penelitian menjelaskan terdapat hubungan antara dukungan keluarga dengan kualitas hidup pasien DM dengan nilai p= 0,0342 dan terdapat hubungan dukungan spiritual dengan kualitas hidup pasien DM dengan p= 0,024. Kesimpulan penelitian ini adalah terdapat hubungan antara dukungan keluarga dan dukungan spiritual dengan kualitas hidup pasien DM. Disarankan untuk mendorong pasien DM untuk aktif dalam kegiatan spiritual yang relevan, seperti doa bersama, konseling spiritual, atau komunitas keagamaan. Kata Kunci: Peran Perawat, Edukator, Kepatuhan Minum Obat, Diabetes Mellitus